PERAN GURU DAN ULAMA SEBAGAI AGEN PEWARISAN NILAI DALAM TRADISI PENDIDIKAN ISLAM MELAYU (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The transmission of values ​​is an important process in Islamic education that focuses not only on the transfer of knowledge, but also on the formation of character, manners, and spiritual awareness of students integrated with local culture. This study aims to analyze the role of teachers and ulama as agents of value transmission in the Malay Islamic educational tradition. This study uses a qualitative approach with a literature study method, through a review of various relevant literature related to the concept of Islamic education, the role of teachers, and the contribution of ulama in Malay society. The results of the study indicate that the transmission of values ​​in Malay Islamic education is based on the integration of the concepts of ta'lim, tarbiyah, and ta'dib which form a holistic education system. Teachers play a primary role in formal education with multidimensional functions as mu'allim, murabbi, mu'addib, muddaris, and mursyid who not only transmit knowledge, but also foster the character and spirituality of students. Meanwhile, ulama play a role in non-formal education through da'wah, recitation, and role models that contribute to maintaining and developing Islamic values ​​in the life of Malay society. In conclusion, the transmission of values ​​in Malay Islamic education is a process involving synergy between teachers and religious scholars in shaping a generation that is knowledgeable, moral, and possesses a strong Islamic and cultural identity. Therefore, strengthening both of these agents is crucial in facing the challenges of modern development, ensuring that Islamic values ​​remain relevant and sustainable.